DEFECT ANALYSIS OF RUBBER PRODUCTS USING FISHBONE AND PARETO CHART METHODS AT CV ANM TECH - Tengku Alfarofi Rajasyah; Adi Rusdi Widya; Bagas Caesar Maulidani (Taksasila Edukasi Insani, 2026)
This research aims to identify the main causes of rubber product defects at CV ANM TECH using the Fishbone Diagram and Pareto Chart methods. The primary issue faced is a high level of product defects, especially due to burning, which impacts quality reduction, customer dissatisfaction, and significant financial losses. Analysis results indicate that product defects are largely caused by poor raw material quality, suboptimal machine settings, inadequate technical training for workers, unmaintained work environment cleanliness, and an ineffective production monitoring system, leading to late detection of new problems. Over 70% of defects are attributed to non-conforming raw materials and operational errors. The study recommends improving raw material management, standardizing work procedures through SOPs, implementing technical training programs for workers, and strengthening quality control to reduce defect rates, enhance efficiency, and bolster the company's competitiveness.Keywords: Rubber products, defects, Fishbone Diagram, Pareto Chart, quality control, CV ANM TECH